The Effect Of Training And Work Motivation On Employee Performance At PT. KSO APS ISS Soekarno-Hatta Airport Area In Tangerang City - Imron Gusroni; Opep Cahya Nugraha (Pasundan Social Science Development, 2025)
This study aims to determine the effect of training and work motivation on employee performance at PT KSO APS ISS Area Soekarno-Hatta Airport in Tangerang City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study training has a significant effect on employee performance of 42.7%, the hypothesis test obtained t count> t table or (8.369> 1.986). Work motivation has a significant effect on employee performance of 38.7%, the hypothesis test obtained t count> t table or (7.707> 1.986). Training and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 8.132 + 0.419X1 + 0.376X2 and an influence contribution of 55.8%, the hypothesis test obtained F count> F table or (58.752> 2.700).